Aerosol size distribution measurement of electronic cigarette emissions using combined differential mobility and inertial impaction methods: Smoking machine and puff topography influence. Issue 11 (2nd November 2018) - Mikheev, Vladimir B.; Ivanov, Alexander; Lucas, Eric A.; South, Patrick L.; Colijn, Hendrik O.; Clark, Pamela I.
Abstract: A combination of a real-time high resolution aerosol differential mobility spectrometer (DMS500) and an electrical low pressure impactor (used as a traditional impactor) was applied to simultaneously collect real-time data and analyze particle size by weighing the mass of the aerosol collected on the impactor stages. Nonrefillable fixed-power as well as refillable and power adjustable e-cigarettes (e-cigs) were tested at various puffing flow rates. Two types of smoking machines were used: a smoke cycle simulator that provides instantaneous straight sample delivery to the analyzer and a Human Profile Pump that utilizes two synchronized pistons and operates by sample pull–push mode. Chemical analysis of the major components of e-liquid (propylene glycol, vegetable glycerol, water, and nicotine) was made using a proton nuclear magnetic resonance method. Limited amounts of samples collected on impactor stages were analyzed by liquid chromatography time-of-flight mass-spectrometry to find newly formed semi- or low-volatile organic compounds in e-cig aerosol and by transmission electron microscopy to check for the presence of nanoparticles in e-cig emissions. Differential mobility and inertial impaction methods showed comparable particle size results. Method of aerosol generation (type of the smoking machine) as well as puffing topography affected the e-cig particle size. Newly formed semi- or low-volatile organic compounds as well as metal nanoparticles were found in e-cig aerosol. Copyright © 2018 American Association for Aerosol Research